Establishing a Tracking System to Monitor Reconstruction Expenditures - Fahmi, A. Zaki (World Bank, Washington, DC, 2012)
In the aftermath of major humanitarian crises, whether caused by natural disasters or conflicts, the international community is increasingly pledging larger amounts of aid to help rebuild devastated regions. At the same time, recipient agencies are called upon to increase the level of accountability and transparency to ensure that the resources they manage are well spent. Large amounts of funding to handle, the need for greater accountability and the increased pressure to improve aid effectiveness intensifies the necessity for reliable information. A tracking system to monitor reconstruction expenditures should monitor all stages of post-crisis reconstruction financial flows, from the initial stage when donors pledge money to actual budget appropriations, and finally to the tracking of disbursements on actual projects. The advantages of such a tracking system are multiple. It enables actors to allocate appropriate funds where it is most needed and to avoid duplications, in terms of both, sector needs and geographic location. Such a system also allows agencies to detect problems early on and to take corrective action as needed, i.e., when there are low levels of spending on projects, or high volatility in the delivery of funds from donors.